If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.66 + 3.33y = 3y + -2 Reorder the terms: 2.66 + 3.33y = -2 + 3y Solving 2.66 + 3.33y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 2.66 + 3.33y + -3y = -2 + 3y + -3y Combine like terms: 3.33y + -3y = 0.33y 2.66 + 0.33y = -2 + 3y + -3y Combine like terms: 3y + -3y = 0 2.66 + 0.33y = -2 + 0 2.66 + 0.33y = -2 Add '-2.66' to each side of the equation. 2.66 + -2.66 + 0.33y = -2 + -2.66 Combine like terms: 2.66 + -2.66 = 0.00 0.00 + 0.33y = -2 + -2.66 0.33y = -2 + -2.66 Combine like terms: -2 + -2.66 = -4.66 0.33y = -4.66 Divide each side by '0.33'. y = -14.12121212 Simplifying y = -14.12121212
| 2+14y=-8+9y | | 2+14y=-8+9 | | 40x^2-65x-30=0 | | 1+6.3z=-2.5 | | -15+x=-27 | | 5*18+9y=45 | | 3x^2=-8x+128 | | 6x^2-x-36=0 | | 2.33+3.33y=3y-4 | | -300=-15k | | -5(1-3r)=28+4r | | 5+2x=4x-13 | | 4n+6+-2n=2(n+3) | | 5x+9*0=45 | | 1+6.33z=-2.5 | | 0.062=-0.06m-0.01 | | x^2-20=-125 | | 85=-5(2r-7) | | 4(3-2n)=n+66 | | -4m-7(6-2m)=22 | | 5*0+9y=45 | | .33x=1.33 | | 8y-12-4y+9=0 | | 8y+7=4y-29 | | 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) |